Language learning motivation and projected desire: an interview study with parents of young language learners. Issue 5 (4th July 2019) - Van Mensel, Luk; Deconinck, Julie
ABSTRACT: Recent studies on language learning motivation have foregrounded notions of identity formation and self-fulfilment. This paper takes two different theoretical frameworks as points of departure (Dörnyei's 'L2 Motivational Self System' and Kramsch's 'desire in language'), but it looks at the motivation/desire of the parents of young language learners, rather than at the learners themselves. Based on in-depth interviews about language and identity with nine parents of various linguistic and social backgrounds in Brussels (Belgium), the data reveal that these parents frequently had vivid mental images of what their multilingual children could achieve in the future (in contrast to their own 'monolingual' achievements). Additionally, they imagined their children having future access to a range of identity options thanks to this multilingual education. In this way, we show that 'desire in language' is not limited to the construction of an inwardly generated identity; it can also be projected outwardly onto other individuals, in this case by parents onto their children.